A study in the production sharing contract in the oil and gas industry and public private partnership in the construction industry / Surya Fareeza A. Rahim - A. Rahim, Surya Fareeza (2013)
The Asian Financial Crisis of 1997 exposed flaws in the Public-Private Partnerships (PPP) arrangements and in turn led to renegotiations and or cancellation of many mega project contracts. The experience left both parties the government and private sector unhappy. Therefore the aim of this study is to understand the application of the current PPP arrangements applied in Malaysia and source alternative methods that could improve it. This research centres on Production Sharing Contract (PSC) an arrangement adapted by the Malaysian National Oil Company (NOC) PETRONAS and compares it to PPP arrangement adapted by the Public Works Department (PWD) of Malaysia. The study of both arrangements led to the construction of a conceptual framework that may improve the current PPP arrangement used in Malaysia. However additional research is suggested to further explore the proposed conceptual framework recommended.